Application of a Stress-Fractional Model for Capturing the Stress-Strain Behavior of Granular Soils - Wei Lu; Jiangong Yang; Jinan Wang (Advances in Civil Engineering)
Granular soils usually serve as the filler material in geotechnical engineering. This study presents the development and application of a stress-fractional model for granular soils with different initial material states. To capture the plastic loading and flow behaviors, a subloading surface with the fractional stress gradient is used. The developed model contains twelve parameters which can be determined through triaxial tests. To validate the developed model, the well-documented test results of Firoozkuh No. 161 sand and crushed basalt are simulated and discussed. It is found that the stress-fractional model can reasonably simulate the undrained and drained behaviors of granular soils consolidated with different densities and mean effective pressures.